Oral health practices of adult inhabitants of a traditional community in Ibadan, Nigeria (2013)
BACKGROUND: Although, the association between oral health care practices and sociodemographic characteristics of populations have been documented, information is sparse on sociodemographic indices influencing oral health practices of residents of traditional communities. The study aimed to describe the oral health practices of adult inhabitants of a traditional community in Nigeria. METHODS: A descriptive, cross-sectional study involving adult residents in randomly selected houses in Idikan, Ibadan, Nigeria. Data on their oral health care practices was obtained with the use of structured interviewer administered questionnaires. Data was analysed with SPSS and test of association carried out using Chi square. RESULTS: A total of 390 adult residents participated in the study, of which 56.2% were males. A total of 196 (50.3%) participants used toothbrush solely to clean their teeth, 72 (18.5%) used chewing sticks alone while 119 (30.5%) used both tooth brush and chewing stick. Older residents of the community, those with no formal education and in lower occupational classes were more likely to use chewing stick (p < 0.05). The majority (68.7%) cleaned their teeth once daily, 30% cleaned twice while 1.3% cleaned infrequently. Educational level attained and occupational class were significantly related to frequency of oral hygiene. Nearly all (95.4%) of the participants knew that oral health Services are available in most hospitals, yet only 35.9% had ever visited a dental Centre with a significantly higher Proportion being males (p < 0.05). CONCLUSION: The study showed that the oral health practices of a typical traditional community in Nigeria are highly influenced by socioeconomic considerations